Country‐Specific Environmental Risks of Fragrance Encapsulates Used in Laundry Care Products. (2nd September 2021) - Cai, Yaping; Lin, Jianming; Gimeno, Sylvia; Begnaud, Frédéric; Nowack, Bernd
Abstract: Fragrance encapsulates (FEs) are designed to deliver fragrance components, notably in laundry care products. They are made of thermoset polymeric shells surrounding the fragrance content. These materials enter the environment mainly during laundry washing, but little is known about their distribution in and impact on the environment. The aim of the present study was to estimate the environmental concentrations of FE shells in freshwater, sediment, and soil compartments for 34 selected countries and to compare them with ecotoxicological effects. Probabilistic material flow analysis was used to estimate worst‐case predicted environmental concentrations (PECs). The lowest freshwater PEC was predicted for Finland (0.00011 µg/L) and the highest for Belgium (0.13 µg/L). Accumulation of FE shells between 2010 and 2019 was considered for sediments and sludge‐treated soils. The PECs in sediments ranged from 3.0 µg/kg (Finland) to 3400 µg/kg (Belgium). For sludge‐treated soil, the concentration was estimated to be between 0 (Malta and Switzerland) and 3600 µg/kg (Vietnam). Ecotoxicological tests showed no effects for FE shells at any tested concentration (up to 2700 µg/L freshwater, 5400 µg/kg sediment, and 9100 µg/kg soil), thus not allowing derivation of a predicted‐no‐effect concentration (PNEC). Therefore, to characterize the environmental risks, the PEC values were compared with highest‐observed‐no‐effect concentrations (HONECs) derived from ecotoxicological tests. The PEC/HONEC ratios were 9.3 × 10 –6, 0.13, and 0.04 for surface waters, sediments, and sludge‐treated soils, respectively, which are much below 1, suggesting no environmental risk. Because the PEC values constitute an upper boundary (no fate considered) and the HONEC values represent a lower boundary (actual PNEC values based on NOECs will be higher), the current risk estimation can be considered a precautionary worst‐case assessment. Environ Toxicol Chem 2022;41:905–916. © 2021 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.